Proper and modern? Discourses about Masculinity - Kahofer, Florian (Momentum Quarterly, 2014)
The present paper deals with representations of masculinity in the Austrian lifestyle magazine for men Wiener. By a corpus-based discourse analysis, a comprehensive body of all issues of the Wiener from the beginning of 2002 to the end of 2012 is investigated. On a theoretical level, Critical Men‘s Studies (CMS) and Feminist Critical Discourse Analysis (FCDA) are presented, dicussed and related to each other. Empirically, a concordance software is employed to analyze concordances of the noun MANN, where the specific examination is limited to nominations in the form of common adjectival phrases. The results show that, aside from discourses on crisis and new masculinity, issues such as age, body or relationship appear. Masculinity is presented as ambivalent and diverse. As a consequence, struggles over the interpretation about manhood can be identified in the texts.
Keywords: Critical Men‘s Studies; corpus linguistics; discourse analysis; lifestyle magazine